Cardiac function in childhood cancer survivors treated with vincristine: Echocardiographic results from the DCCSS LATER 2 CARD study. (15th December 2022) - Merkx, Remy; Feijen, E. (Lieke) A.M.; Leerink, Jan M.; de Baat, Esmée C.; Bellersen, Louise; van Dalen, Elvira C.; van Dulmen-den Broeder, Eline; van der Heiden-van der Loo, Margriet; van den Heuvel-Eibrink, Marry M.; de Korte, Chris L.; Loonen, Jacqueline; Louwerens, Marloes; et al.
Abstract: Background: Anthracyclines and radiotherapy involving the heart region are cardiotoxic, but the potential cardiotoxicity of vincristine remains unknown. We assessed cardiac function in vincristine-treated >5-year childhood cancer survivors (CCS). Methods and results: We cross-sectionally compared echocardiograms of 101 vincristine-treated CCS (median age 35 years [range: 17–53], median vincristine dose 63 mg/m 2 ) from the national Dutch Childhood Cancer Survivor Study, LATER cohort, to 101 age- and sex-matched controls. CCS treated with anthracyclines, radiotherapy involving the heart region, cyclophosphamide or ifosfamide were excluded. Twelve CCS (14%) versus four controls (4%; p 0.034) had a decreased left ventricular ejection fraction (LVEF; men <52%, women <54%). Mean LVEF was 58.4% versus 59.7% ( p 0.050). Global longitudinal strain (GLS) was abnormal in nineteen (24%) CCS versus eight controls (9%; p 0.011). Mean GLS was 19.0% versus 20.1% ( p 0.001). No ≥grade 2 diastolic dysfunction was detected. In multivariable logistic regression analysis CCS had higher risk of abnormal GLS (OR 3.55, p 0.012), but not abnormal LVEF (OR 3.07, p 0.065), than controls. Blood pressure and smoking history contributed to variation in LVEF, whereas obesity and diastolic blood pressure contributed to variation in GLS. Cumulative vincristine dose was not associated with either abnormal LVEF or abnormal GLS in multivariable models corrected for age and sex (OR per 50 mg/m 2 : 0.88, p 0.85 and 1.14, p 0.82, respectively). Conclusions: Vincristine-treated long-term CCS showed an abnormal GLS more frequently than controls. Their risk for future clinical cardiac events and the role of risk factor modification should be further elucidated. Graphical abstract: Unlabelled Image Highlights: Echocardiographic GLS measurement may detect cardiac dysfunction in an early stage Vincristine-treated childhood cancer survivors show reduced GLS No dose-response relation was present between vincristine dose and LVEF or GLS Diastolic blood pressure and body mass index contributed to lower GLS Whether these survivors are at risk for cardiovascular events should be elucidated